Preparation method of additive for improving performance of low-rubber-material machine-made sand concrete

Through the combination of modified zeolite and gas induction agent and cellulose, the problems of easy separating, water-excreting, large shrinkage and harmful ion erosion of low-glue sand concrete are solved, and a variety of properties of concrete are improved, including water retention and pressure resistance. Strength and anti-chlorine ion penetration properties.

CN119191748APending Publication Date: 2024-12-27ANHUI RUIHE NEW MATERIALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411307588.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Due to the low content of water-washed sand concrete, the poor particle size, the problems of separating water secretion, large shrinkage, and harmful ion erosion, the existing technology has failed to effectively solve its multi-performance target regulation.

Method used

Immerse zeolite with zinc nitrate solution, high-temperature calcination and high-energy ball mill to prepare modified zeolites, and mix them with gas induction agent and cellulose to form low-glue machine sand concrete performance improvement additives, improve the water retention of concrete and resist harmful ion erosion. Performance and compactness.

Benefits of technology

The water retention, ease, volume stability, and anti-toxic ion corrosion performance of low-glue machine sand concrete is significantly improved, and the frost resistance and compactness of concrete is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005049718840000071
    Figure BDA0005049718840000071
Patent Text Reader

Abstract

The invention provides a preparation method of an admixture for improving the performance of low-gel machine-made sand concrete, which comprises the following steps: carrying out impregnation reaction on zeolite and a zinc nitrate solution with the mass concentration of 4% at the impregnation temperature of 80 DEG C for 3.5 hours, and fully stirring in the impregnation process; roasting the solution at a high temperature of 300-400 DEG C, and drying; the dried product is subjected to high-energy ball milling, the appropriate ball milling time is that the average particle size is controlled to be 5-10 [mu] m, and the obtained powder is modified zeolite; and fully mixing the air entraining agent, the cellulose and the modified zeolite to obtain the air entraining agent. The invention aims to improve the water-retaining property, the volume stability, the chemical erosion and corrosion resistance and the freeze-thaw resistance of the low-gel-material machine-made sand concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional admixture preparation, and specifically relates to a method for preparing an admixture for improving the performance of low-adhesive machine-made sand concrete. Background Art

[0002] With the vigorous development of infrastructure construction in my country, the demand for concrete is huge. At the same time, due to the non-renewable nature of aggregate resources and the increasing efforts in environmental protection in my country, natural sand can no longer meet the needs of engineering construction, and there is even a situation where there is no sand available. As a potential alternative to natural river sand, machine-made sand has gradually become the main fine aggregate in engineering concrete. A large number of practices have proved that compared with river sand, machine-made sand has obvious problems such as poor particle grading, many edges and corners, and needle-like particles. Moreover, with the increasing efforts of environmental protection to control dust, most concrete currently uses water-washed machine-made sand produced by wet method. In the production process of water-washed machine-made sand, powder with a particle size of less than 0.075mm and even fine particles with a particle size of more than 0.15mm are also removed, making the fineness modulus of water-washed machine-made sand larger, even as high as 3.5.

[0003] Based on the above characteristics of machine-made sand and when the amount of cementitious materials is relatively low, the prepared machine-made sand concrete has certain limitations in workability and compactness. Poor workability is mainly manifested in the easy separation and bleeding of concrete, which makes it difficult to pump concrete for construction, and indirectly affects the mechanical properties and durability of concrete; poor compactness makes concrete susceptible to harmful ion corrosion, which has serious harm to the durability of concrete. A large number of studies have shown that compared with concrete prepared with natural sand, the volume stability of machine-made sand concrete is relatively poor, which is manifested as easy shrinkage and large cracking.

[0004] The existing technology has a relatively single solution to the above-mentioned problems, and has not considered the multi-performance target regulation of machine-made sand concrete. The water-retaining agent used in Patent 201410255852.5 to inhibit water seepage is relatively single in type, and the effect of inhibiting water seepage is limited. Moreover, the addition of sodium sulfate will cause the slump loss of concrete to increase over time. At the same time, the patent does not consider the volume stability and durability of machine-made sand concrete. Patent 202211025652.1 also focuses on the preparation of water-retaining agents to improve the working performance of concrete. It has a single component and relatively single performance regulation. Patent 202110713227.0 takes into account the working performance and volume stability of machine-made sand concrete, but the machine-made sand used is medium sand with a fineness modulus of 2.5, and the content below 0.15 mm is relatively high. At the same time, the resistance to harmful ion corrosion is not considered.

[0005] Therefore, in view of the problems of poor workability, poor volume stability and easy erosion of harmful ions in low-binder machine-made sand concrete, it is necessary to develop an admixture with multiple performance improvement goals to comprehensively solve the problems of the above-mentioned machine-made sand concrete in view of the shortcomings of the existing technology. Summary of the invention

[0006] In view of the above problems and the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a low-cement machine-made sand concrete performance improving admixture to solve the problems of segregation, water seepage, large shrinkage, and harmful ion erosion in machine-made sand concrete caused by low content of water-washed machine-made sand and stone powder, poor particle shape, and low amount of cementitious materials.

[0007] In order to achieve the above object, the present invention adopts the following technical scheme to achieve a method for preparing a low-adhesive machine-made sand concrete performance improving admixture, characterized in that it comprises the following steps:

[0008] (1) impregnating the zeolite with a zinc nitrate solution having a mass concentration of 4% at a temperature of 80° C. for 3.5 hours, and stirring the solution sufficiently during the impregnation process;

[0009] (2) calcining the solution formed in step (1) at a high temperature of 300° C. to 400° C. and drying;

[0010] (3) subjecting the dried product of step (2) to high-energy ball milling, wherein the ball milling time is preferably controlled so that the average particle size is between 5 μm and 10 μm, and the obtained powder is a modified zeolite;

[0011] (4) The air entraining agent and the modified zeolite obtained in step (3) are fully mixed for 10 minutes, and then cellulose is added and fully mixed for 10 minutes. The obtained powder is a performance improving admixture for low-colloid machine-made sand concrete.

[0012] The zeolite is natural zeolite, and the average particle size of the zeolite is between 10um and 20um.

[0013] The mass ratio of the zeolite to the zinc nitrate solution is 1:2.5-7.5.

[0014] The air entraining agent is any one of triterpenoid saponin and sodium dodecyl sulfate or a mixture of any one or more of them in any proportion.

[0015] The cellulose is any one of hydroxyethyl cellulose and hydroxypropyl methyl cellulose or a mixture of any proportion of the above cellulose.

[0016] The mass ratio of modified zeolite, air entraining agent and cellulose in the low-adhesive machine-made sand concrete performance improving admixture is 100:0.02-0.2:0.01-0.1.

[0017] Compared with the prior art, the admixture composition disclosed in the present invention for improving the anti-corrosion and rust-resistant performance of concrete has the following advantages:

[0018] 1. The modified zeolite prepared by the present invention integrates multiple functions such as water retention, internal curing, volcanic ash effect, adsorption, ion exchange capacity, etc., which can significantly improve the water retention, workability, volume stability, strength performance and resistance to harmful ions (SO4 2- , Cl - ) Corrosion performance.

[0019] 2. The present invention combines the characteristics of zeolite to introduce targeted adsorption active groups of zinc oxide, which increases the surface active sites of zeolite and increases the zeolite's ability to absorb anions (SO4 2- , Cl - )'s selective adsorption capacity further enhances the concrete's resistance to harmful ion corrosion.

[0020] 3. The zeolite used in the present invention has the characteristics of high content of active silicon dioxide and aluminum oxide, good reaction activity and low cost. It undergoes secondary hydration reaction with the hydration product calcium hydroxide, greatly consuming the content of the corroded product calcium hydroxide, and generating more hydrated calcium silicate gel, further improving the density and corrosion resistance of the concrete.

[0021] 4. The zeolite used in the present invention has excellent internal curing performance, which can significantly reduce the shrinkage of low-colloid machine-made sand concrete and improve the volume stability of concrete.

[0022] 5. The modified zeolite prepared by the present invention, when used in combination with an air entraining agent and cellulose, has a good synergistic effect in terms of water retention and flow properties, can greatly improve the water retention and flow properties of low-colloid machine-made sand concrete, and enhance the frost resistance and durability of concrete. DETAILED DESCRIPTION

[0023] In order to further illustrate the content of the present invention, the technical scheme of the present invention is further described through the following specific examples. The present invention evaluates the prepared product through technical parameters such as slump, expansion, water bleeding rate, 28d compressive strength, 28d shrinkage, chloride ion migration coefficient, and sulfate corrosion resistance coefficient of low-glue machine-made sand concrete.

[0024] Example 1

[0025] A preparation method for a low-adhesive machine-made sand concrete performance improving admixture comprises the following steps: taking a natural zeolite and a zinc nitrate solution with a mass concentration of 4% in a mass ratio of 1:2.5, carrying out an impregnation reaction, the impregnation temperature being 80°C, the impregnation time being 3.5 hours, and fully stirring during the impregnation process; calcining the solution at a high temperature of 300°C and drying; grinding the dried solid to a particle size of 5 μm to 10 μm to obtain a modified zeolite powder; fully mixing triterpenoid saponin with the modified zeolite for 10 minutes, then adding hydroxyethyl methyl cellulose and fully mixing for 10 minutes, and the mass ratio of modified zeolite: triterpenoid saponin: hydroxyethyl methyl cellulose being 100:0.02:0.01, and the obtained powder is the low-adhesive machine-made sand concrete performance improving admixture.

[0026] Example 2

[0027] A preparation method for a low-adhesive machine-made sand concrete performance improving admixture comprises the following steps: taking a natural zeolite and a zinc nitrate solution with a mass concentration of 4% in a mass ratio of 1:7.5, carrying out an impregnation reaction, the impregnation temperature being 80°C, the impregnation time being 3.5 hours, and fully stirring during the impregnation process; calcining the solution at 300°C and drying; grinding the dried solid to a particle size of 5 μm to 10 μm to obtain a modified zeolite powder; fully mixing triterpenoid saponin with the modified zeolite for 10 minutes, then adding hydroxyethyl methyl cellulose and fully mixing for 10 minutes, and the mass ratio of modified zeolite: triterpenoid saponin: hydroxyethyl methyl cellulose being 100:0.02:0.01, and the obtained powder is the low-adhesive machine-made sand concrete performance improving admixture.

[0028] Example 3

[0029] A preparation method for a low-adhesive machine-made sand concrete performance improving admixture comprises the following steps: taking a natural zeolite and a zinc nitrate solution with a mass concentration of 4% in a mass ratio of 1:5.0, carrying out an impregnation reaction, the impregnation temperature being 80°C, the impregnation time being 3.5 hours, and fully stirring during the impregnation process; calcining the solution at a high temperature of 300°C and drying; grinding the dried solid to a particle size of 5 μm to 10 μm to obtain a modified zeolite powder; fully mixing triterpenoid saponin with the modified zeolite for 10 minutes, then adding hydroxyethyl methyl cellulose and fully mixing for 10 minutes, and the mass ratio of modified zeolite: triterpenoid saponin: hydroxyethyl methyl cellulose being 100:0.02:0.01, and the obtained powder is the low-adhesive machine-made sand concrete performance improving admixture.

[0030] Example 4

[0031] A preparation method for a low-adhesive machine-made sand concrete performance improving admixture comprises the following steps: taking a natural zeolite and a zinc nitrate solution with a mass concentration of 4% in a mass ratio of 1:5.0, carrying out an impregnation reaction, the impregnation temperature being 80°C, the impregnation time being 3.5 hours, and fully stirring during the impregnation process; calcining the solution at a high temperature of 300°C and drying; grinding the dried solid to a particle size of 5 μm to 10 μm to obtain a modified zeolite powder; fully mixing triterpenoid saponin with the modified zeolite for 10 minutes, then adding hydroxyethyl methyl cellulose and fully mixing for 10 minutes, and the mass ratio of modified zeolite: triterpenoid saponin: hydroxyethyl methyl cellulose being 100:0.02:0.01, and the obtained powder is the low-adhesive machine-made sand concrete performance improving admixture.

[0032] Example 5

[0033] A preparation method for a low-adhesive machine-made sand concrete performance improving admixture comprises the following steps: taking a natural zeolite and a zinc nitrate solution with a mass concentration of 4% in a mass ratio of 1:5.0, carrying out an impregnation reaction, the impregnation temperature being 80°C, the impregnation time being 3.5 hours, and fully stirring during the impregnation process; calcining the solution at a high temperature of 300°C and drying; grinding the dried solid to a particle size of 5 μm to 10 μm to obtain a modified zeolite powder; fully mixing triterpenoid saponin with the modified zeolite for 10 minutes, then adding hydroxyethyl methyl cellulose and fully mixing for 10 minutes, and the mass ratio of modified zeolite: triterpenoid saponin: hydroxyethyl methyl cellulose being 100:0.02:0.01, and the obtained powder is the low-adhesive machine-made sand concrete performance improving admixture.

[0034] Example 6

[0035] A preparation method for a low-adhesive machine-made sand concrete performance improving admixture comprises the following steps: taking a natural zeolite and a zinc nitrate solution with a mass concentration of 4% in a mass ratio of 1:5.0, carrying out an impregnation reaction, the impregnation temperature being 80°C, the impregnation time being 3.5 hours, and fully stirring during the impregnation process; calcining the solution at a high temperature of 300°C and drying; grinding the dried solid to a particle size of 5 μm to 10 μm to obtain a modified zeolite powder; fully mixing triterpenoid saponin with the modified zeolite for 10 minutes, then adding hydroxyethyl methyl cellulose and fully mixing for 10 minutes, and the mass ratio of modified zeolite: triterpenoid saponin: hydroxyethyl methyl cellulose being 100:0.02:0.01, and the obtained powder is the low-adhesive machine-made sand concrete performance improving admixture.

[0036] Example 7

[0037] A preparation method for a low-adhesive machine-made sand concrete performance improving admixture comprises the following steps: taking a natural zeolite and a zinc nitrate solution with a mass concentration of 4% in a mass ratio of 1:5.0, carrying out an impregnation reaction, the impregnation temperature being 80°C, the impregnation time being 3.5 hours, and fully stirring during the impregnation process; calcining the solution at a high temperature of 300°C and drying; grinding the dried solid to a particle size of 5 μm to 10 μm to obtain a modified zeolite powder; fully mixing triterpenoid saponin with the modified zeolite for 10 minutes, then adding hydroxyethyl methyl cellulose and fully mixing for 10 minutes, and the mass ratio of modified zeolite: triterpenoid saponin: hydroxyethyl methyl cellulose being 100:0.02:0.01, and the obtained powder is the low-adhesive machine-made sand concrete performance improving admixture.

[0038] Example 8

[0039] A preparation method for a low-adhesive machine-made sand concrete performance improving admixture comprises the following steps: taking a natural zeolite and a zinc nitrate solution with a mass concentration of 4% in a mass ratio of 1:5.0, carrying out an impregnation reaction, the impregnation temperature being 80°C, the impregnation time being 3.5 hours, and fully stirring during the impregnation process; calcining the solution at 300°C and drying; grinding the dried solid to a particle size of 5 μm to 10 μm to obtain a modified zeolite powder; mixing sodium dodecyl sulfate and the modified zeolite for 10 minutes, then adding hydroxyethyl methyl cellulose and mixing for 10 minutes, and the mass ratio of the modified zeolite: triterpenoid saponin: hydroxyethyl methyl cellulose is 100:0.02:0.01, and the obtained powder is the low-adhesive machine-made sand concrete performance improving admixture.

[0040] Example 9

[0041] A preparation method for a low-adhesive machine-made sand concrete performance improving admixture comprises the following steps: taking a natural zeolite and a zinc nitrate solution with a mass concentration of 4% in a mass ratio of 1:5.0, carrying out an impregnation reaction, the impregnation temperature being 80°C, the impregnation time being 3.5 hours, and fully stirring during the impregnation process; calcining the solution at a high temperature of 300°C and drying; grinding the dried solid to a particle size of 5 μm to 10 μm to obtain a modified zeolite powder; fully mixing triterpenoid saponin with the modified zeolite for 10 minutes, then adding hydroxypropyl methylcellulose and fully mixing for 10 minutes, and the mass ratio of modified zeolite: triterpenoid saponin: hydroxyethyl methylcellulose being 100:0.02:0.01, and the obtained powder is the low-adhesive machine-made sand concrete performance improving admixture.

[0042] Comparative Example 1

[0043] The benchmark group is concrete without the product prepared by the present invention.

[0044] Comparative Example 2

[0045] The method is basically the same as Example 1, except that the mass ratio of natural zeolite to zinc nitrate solution with a mass concentration of 4% is 1:2.0.

[0046] Comparative Example 3

[0047] The method is basically the same as Example 2, except that the mass ratio of natural zeolite to zinc nitrate solution with a mass concentration of 4% is 1:8.0.

[0048] Comparative Example 4

[0049] The method is basically the same as Example 3, except that the mass ratio of modified zeolite: triterpenoid saponin: hydroxyethyl methyl cellulose is 100:0.01:0.01.

[0050] Comparative Example 5

[0051] The method is basically the same as Example 3, except that the mass ratio of modified zeolite: triterpenoid saponin: hydroxyethyl methyl cellulose is 100:0.02:0.005.

[0052] Comparative Example 6

[0053] The method is basically the same as Example 6, except that the mass ratio of modified zeolite: triterpenoid saponin: hydroxyethyl methyl cellulose is 100:0.25:0.1.

[0054] Comparative Example 7

[0055] The method is basically the same as Example 6, except that the mass ratio of modified zeolite: triterpenoid saponin: hydroxyethyl methyl cellulose is 100:0.2:0.15.

[0056] Implementation Effect

[0057] The present invention aims to improve various properties of low-glue machine-made sand concrete by introducing a component integrating multiple functions to solve various problems of machine-made sand concrete, such as segregation, water seepage, large shrinkage, and harmful ion erosion.

[0058] Comparative test of low-binder machine-made sand concrete performance: The amount of each raw material in the concrete mix ratio is Xinning P·O42.5 cement 231kg / m 3 , Jianbi II fly ash 99kg / m 3 、Machinery sand 845kg / m 3 , 5mm~31.5mm continuous graded crushed stone 1033kg / m 3 、Water 162kg / m 3 , Polycarboxylic acid high performance water reducing agent 3.96kg / m 3The dosage of the admixture of the present invention is 5% of the mass of the cementitious material, wherein the fineness modulus of the machine-made sand is 3.3, and the content below 0.15 mm is 5.8%. The slump, expansion and water seepage rate tests are carried out in accordance with the provisions of GB / T 50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", the compressive strength test is carried out in accordance with the provisions of GB / T 50081-2019 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", the shrinkage rate, chloride ion migration coefficient and sulfate corrosion resistance coefficient test are carried out in accordance with the provisions of GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", and the specific performance test results are shown in Table 1. It can be seen from the results in Table 1 that, compared with Comparative Example 1, the concrete fluidity, water retention, compressive strength, shrinkage, chloride ion penetration resistance and sulfate corrosion resistance of Examples 1 to 9 are significantly improved; Compared with Example 1, Example 2 has a slightly lower water retention performance, a chloride ion migration coefficient increased by 16.3%, and a sulfate corrosion resistance coefficient decreased by 11.0%; Compared with Example 2, Example 3 has a slightly lower water retention performance, a chloride ion migration coefficient increased by 20.1%, and a sulfate corrosion resistance coefficient decreased by 14.9% compared with Example 2; Compared with Comparative Examples 4 and 5, Example 3 has a slightly lower water retention performance, a chloride ion migration coefficient increased by 20.1%, and a sulfate corrosion resistance coefficient decreased by 14.9%. Compared with Example 3, the fluidity of Comparative Example 4 is reduced to a certain extent, wherein the expansion is reduced by 10.6%, the water bleeding rate is increased by 192.3%, and other properties are not greatly affected. The fluidity of Comparative Example 5 is significantly reduced, wherein the expansion is reduced by 19.1%, the water bleeding rate is increased by 230.8%, and other properties are not greatly affected. Compared with Comparative Examples 6 and 7, Example 6 has a 28d compressive strength reduced by 17.6% compared with Example 6, and other properties are less affected. The fluidity of Comparative Example 7 is reduced to a certain extent, wherein the expansion is reduced by 22.2%, the 28d compressive strength is reduced by 13.2%, and other properties are not greatly affected.

[0059]

[0060] Although the present invention lists some embodiments as disclosed above, they are not intended to limit the present invention. Anyone familiar with this technology can make various changes or modifications without departing from the spirit and scope of the present invention. For example, adding or reducing a certain raw material component or process time may not have a substantial impact on the effect of the product. In this case, such changes also fall within the scope defined by the scope of protection of the claims of this application.

Claims

1. A method for preparing a low-binder machine-made sand concrete performance improving admixture, characterized in that: The following steps are involved: Step 1: impregnate the zeolite with a zinc nitrate solution with a mass concentration of 4% at a temperature of 80° C. for 3.5 hours, and stir the solution sufficiently during the impregnation process; Step 2: calcining the solution formed in step 1 at a high temperature of 300° C. to 400° C. and drying; Step 3: subjecting the product formed in step 2 to high-energy ball milling until the average particle size is 5 μm to 10 μm, and the obtained powder is a modified zeolite; Step 4: First, fully mix the air-entraining agent with the modified zeolite obtained in step 3 for 10 minutes, and then add cellulose and mix them for 10 minutes. The resulting powder is the performance improvement admixture for low-colloid machine-made sand concrete.

2. The method for preparing the low-glue machine-made sand concrete performance improving admixture according to claim 1, characterized in that: The zeolite is natural zeolite, and the average particle size of the zeolite is 10um to 20um.

3. The method for preparing the low-glue machine-made sand concrete performance improving admixture according to claim 1, characterized in that: The mass ratio of the zeolite to the zinc nitrate solution is 1:2.5-7.

5.

4. The method for preparing the low-glue machine-made sand concrete performance improving admixture according to claim 1, characterized in that: The air entraining agent is any one of triterpenoid saponin and sodium dodecyl sulfate or a mixture of any one or more of them in any proportion.

5. The method for preparing the low-glue machine-made sand concrete performance improving admixture according to claim 1, characterized in that: The cellulose is any one of hydroxyethyl cellulose and hydroxypropyl methyl cellulose or a mixture of any proportion of the above cellulose.

6. The method for preparing the low-glue machine-made sand concrete performance improving admixture according to claim 1, characterized in that: The mass ratio of modified zeolite, air entraining agent and cellulose in the low-adhesive machine-made sand concrete performance improving admixture is 100:0.02-0.2:0.01-0.1.